2009
DOI: 10.1073/pnas.0900893106
|View full text |Cite
|
Sign up to set email alerts
|

Water may inhibit oxygen binding in hemoprotein models

Abstract: Three distal imidazole pickets in a cytochrome c oxidase (CcO) model form a pocket hosting a cluster of water molecules. The cluster makes the ferrous heme low spin, and consequently the O2 binding slow. The nature of the rigid proximal imidazole tail favors a high spin/low spin cross-over. The O2 binding rate is enhanced either by removing the water, increasing the hydrophobicity of the gas binding pocket, or inserting a metal ion that coordinates to the 3 distal imidazole pickets.spin cross-over ͉ tris-imida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…electron transfer rate ͉ oxygen binding rates ͉ water cluster ͉ oxygen complex stabilization ͉ partially reduced oxygen species A recent report showed that water may inhibit oxygen binding in hemoprotein models (1). This echoes the ''water displacement model'' proposed for oxygen binding in myoglobin (2)(3)(4).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…electron transfer rate ͉ oxygen binding rates ͉ water cluster ͉ oxygen complex stabilization ͉ partially reduced oxygen species A recent report showed that water may inhibit oxygen binding in hemoprotein models (1). This echoes the ''water displacement model'' proposed for oxygen binding in myoglobin (2)(3)(4).…”
mentioning
confidence: 65%
“…However, the amount of PROS formed with the picket fence 4 is twice the amount formed with the Trisimidazole 3. Note that the measure of PROS is a percentage of the total current generated and, hence, does not reflect the number of turnovers associated with slower oxygen binding rates as was found in the Tris-imidazole model 3 (1). Altogether these facts suggest that the nature of the superstructure may play a significant but surprising role in preventing the release of the oxygen complex (or other partially reduced oxygen species), making 3 more stable to hydrolytic formation of PROS than the picket fence 4.…”
Section: Resultsmentioning
confidence: 99%
“…38,40 Note that imidazole and water bound LS Fe II species, although proposed in some synthetic systems, are yet to be structurally characterized. 47,48 …”
Section: Results and Analysismentioning
confidence: 99%
“…6,28 The slower reactivity of those synthetic heme-Cu systems may be due to a slower rate of O 2 binding to the 6C LS reduced iron center. 28,47,51 …”
Section: Results and Analysismentioning
confidence: 99%
“…This conclusion is largely supported on the basis of comparison to 46a, which reacts slower than its dinuclear counterpart [136]. In aqueous systems, the presence of copper has also been suggested to play a role in protecting the iron center against the coordination of water, which has been shown to significantly inhibit the binding of O 2 by effecting a high-to low-spin crossover [137].…”
Section: (μ-Peroxo)iron-copper Intermediatesmentioning
confidence: 95%